The function and significance of SELENBP1 downregulation in human bronchial epithelial carcinogenic process. - Gu-Qing Zeng; Hong Yi; Peng-Fei Zhang; Xin-Hui Li; Rong Hu; Mao-Yu Li; Cui Li; Jia-Quan Qu; Xingming Deng; Zhi-Qiang Xiao (PLoS ONE)
Background Our quantitative proteomic study showed that selenium-binding protein 1 (SELENBP1) was progressively decreased in human bronchial epithelial carcinogenic process. However, there is little information on expression and function of SELENBP1 during human lung squamous cell cancer (LSCC) carcinogenesis. Methods iTRAQ-tagging combined with 2D LC-MS/MS analysis was used to identify differentially expressed proteins in the human bronchial epithelial carcinogenic process. SELENBP1, member of selenoproteins family and progressively downregulated in this process, was selected to further study. Both Western blotting and immunohistochemistry were performed to detect SELENBP1 expression in independent sets of tissues of bronchial epithelial carcinogenesis, and ability of SELENBP1 for discriminating NBE (normal bronchial epithelium) from preneoplastic lesions from invasive LSCC was evaluated. The effects of SELENBP1 downregulation on the susceptibility of benzo(a)pyrene (B[a]P)-induced human bronchial epithelial cell transformation were determined. Results 102 differentially expressed proteins were identified by quantitative proteomics, and SELENBP1 was found and confirmed being progressively decreased in the human bronchial epithelial carcinogenic process. The sensitivity and specificity of SELENBP1 were 80% and 79% in discriminating NBE from preneoplastic lesions, 79% and 82% in discriminating NBE from invasive LSCC, and 77% and 71% in discriminating preneoplastic lesions from invasive LSCC, respectively. Furthermore, knockdown of SELENBP1 in immortalized human bronchial epithelial cell line 16HBE cells significantly increased the efficiency of B[a]P-induced cell transformation. Conclusions The present data shows for the first time that decreased SELENBP1 is an early event in LSCC, increases B[a]P-induced human bronchial epithelial cell transformation, and might serve as a novel potential biomarker for early detection of LSCC.